Neurobehavioral evaluation and phytochemical characterization of a series of argentine valerian species - Marcucci, Carolina; Anselmi Relats, Juan Manuel; Bach, Hernán Gerónimo; Kamecki, Fabiola; Varela, Beatriz Graciela; Wagner, Marcelo L.; Pastore, Valentina; Colettis, Natalia; Ricco, Rafael A.; Marder, Mariel (Elsevier, 2020)
Folkloric or galenic preparations of valerian roots and rhizomes have been used as sedatives/anxiolytics and sleep inducers since ancient times. “Valerianas” are plants that naturally grow in our region. Although some of them are used in folk medicine, they lack scientific information. We performed a comparative study of the phytochemical composition and the potential in vivo effects of ethanolic extracts of argentine valerian species: Valeriana carnosa Sm., V. clarionifolia Phil. and V. macrorhiza Poepp. ex DC., from “Patagonia Argentina”; V. ferax (Griseb.) Höck and V. effusa Griseb., from the central part of our country, and V. officinalis (as the reference plant). All these plants were rich in phenolic compounds, evidenced the presence of ligands for the benzodiazepine binding site of the GABAA receptor and were able to induce sedation as assessed by loss-of-righting reflex assays (500 mg/kg, i.p.). Mice treated with V. macrorhiza, V. carnosa and V. ferax extracts showed reduced exploratory behaviors while V. clarionifolia produced anxiolytic-like activities (500 mg/kg, i.p.) in the Hole board test. Oral administrations (300 mg/kg and 600 mg/kg, p.o.) evidenced sedative effects for V. ferax and anxiolytic-like properties for V. macrorhiza, V. carnosa and V. clarionifolia extracts. Our native valerian species are active on the CNS, validating its folkloric use as anxiolytic/sedative and sleep enhancers.